ROBOTOTEXNIKA FANINI O‘QITIShDA TINKERCAD PLATFORMASINING IMKONIYATLARI - Saloxidinova, D.S.; Ziyadullaev, D.Sh. (SCIENCE and SOCIETY, 2025)
The article shows the specific methodology of the practical training of making smart lighting in the 7th grade “Technology” Science “Robotics” Module and methodological recommendations for Doric problems related to robotics science. This methodology was used in practice to statistically determine the efficiency coefficient.